Influence of the geometric factor for the width of the contour scan in selective laser melting - Ahn, Il Hyuk (2016)
Selective laser melting (SLM) is one of additive manufacturing technologies and based on the metallic powders. SLM process can fabricate a part with high geometric complexity with layer-by-layer fashion. During the process, there are two types of laser scans as their rules. Among them, contour scan makes the contour of a part and is mainly responsible for the surface quality like a surface roughness, and geometric/dimensional accuracy of a part. In viewpoint of the dimensional accuracy, the accurate estimation of the width in the contour scan is important. It has been known that the width is affected by process parameters related to the energy density such as laser power and scan speed. However, it should be noted that the width can be changed with the shape of a path for the contour scan due to the change of the exposure time as change of the scan direction. In this study, to estimate the influence of the exposure time for the width, specimens with thin wall and circular shape are fabricated on the different scan speed. The width of fabricated parts is measured. The measured results shows that the width decreases with the diameter of the circle. It proves that the geometric factor affects the dimensional accuracy as the change of the width.